# Given y = (2x + 3)^{2}, represent it in the standard form of the given quadratic equation.

Quadratic equations are equations that have a degree equal to two. They are represented as a parabola on the graph.

## Answer: The standard form of the given equation y = (2x + 3)^{2} is y = 4x^{2} + 12x + 9.

Let's understand the solution in detail.

**Explanation:**

Given quadratic equation: y = (2x + 3)^{2}.

Now, the standard form of a quadratic equation is given by y = ax^{2} + bx + c.

Now, to represent the given equation in standard form, we use the identity - (a + b)^{2}.

Hence, (2x + 3)^{2} = (2x)^{2} + (2 × 2x × 3) + 3^{2} = 4x^{2} + 12x + 9.

Hence, it is in the standard form y = ax^{2} + bx + c, where a = 4, b = 12 and c = 9.